The correlation between serum levels of soluble platelet -selectin in preeclampsia with & without intrauterine growth retardation versus normal pregnancy - AL-Maini, Esraa H.; Ali, Sarah I. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: preeclampsia is characterized by endothelial dysfunction with vasoconstriction due to cell adhesion molecules or mediators released by defective placentation. Soluble platelet selectin, one of the cell adhesion molecules, is elevated in many inflammatory conditions including preeclampsia. Objective: To investigate if soluble platelet-selectin levels can be used as a marker for adverse outcomes in pregnancy complicated with sever preeclampsia Patients and methods:This study involved 115 pregnant women in their third trimester of pregnancy; divided into Group A: involves 25 pregnant women with preeclampsia complicated by intrauterine growth restriction.Group B: involves 35 pregnant women with preeclampsia without intrauterine growth restriction.Control group: involve 55 pregnant women with normal blood pressure and normal fetal growth .The data were conducted from patients by special questionnaire, this involve name, age, parity, examination included vital signs, abdominal, obstetrical examination and investigations including :Liver function test, Renal function test, Complete blood picture and maternal serum levels of soluble platelet selectin was measured by enzyme-linked immunosorbent assay ,albumin in urine and serial obstetrical ultrasound scan to confirm the diagnosis of intrauterine growth retardation and Doppler study to determine fetuses at risk . Results: this study revealed a significantly higher concentration of soluble platelet selectin levels in serumofpreeclamptic women with and without intrauterine growth retardation versus normotensive and normal fetal growth. The maternal serum levels of sP-selectin in preeclampsia without intrauterine growth restriction were significantly higher than preeclampsia complicated by intrauterine growth restriction .Sensitivity was 91.7% and specificity 100% at cut off value 6.975 ng/ml of maternal soluble platelet _selectin for prediction of adverse pregnancy outcome . Conclusion: soluble platelet -selectin levels have a positive significant correlation with the severity of preeclampsia, so it can beconsidered as a marker for its severity and can be used as a predictor for adverse outcomes as itsnegatively correlated with these complications